A Note on the Effect of Aqueous Filtrates of Argel Plant Parts (Solenostemma argel, Del Hyne) on the Mortality of Cotton Soil Termite (Microtermes thoracalis Sjost.) (Isoptera: Termitidae) - Sidahmed, Omar A.A.; Eldoush, Khalid O.A.M.; Taha, Awad Khalafalla (University of Khartoum Journal of Agricultural Sciences, 2023)
A laboratory experiment was carried out to evaluate the efficacy of three concentrations (5 %, 7.5 % and 10 %) of aqueous filtrate of argel (Solenostemma argel) against workers and soldiers of the cotton soil termite (Microtermes thoracalis). The synthetic insecticide Morisban 4 was used as a standard. Statistical analysis showed significant differences between the tested concentrations of argel aqueous filtrates and Morisban 4 compared with the untreated control. The highest concentration (10%) of argel aqueous filtrates and Morisban 4 gave 100% mortality for termites. The study proved the suitability of argel parts for controlling termites, and represents a good environmental and alternative method for synthetic insecticides of termites.